Les jeux d’échelle dans la communication politique des présidents des régions italiennes de l’Émilie-Romagne et du Latium. Une approche par la statistique textuelle - Dorian Bernadou (Belgeo)
In December 2016, Italy’s failed referendum highlighted the question of the place of regions in the Italian institutional landscape. Nearly twenty years ago, a series of changes to the country's Constitution marked a decisive turn toward federalism and regional level empowerment, with a President elected by direct universal suffrage. In their last political speeches, regional executives are allowed to develop a more personal and subjective vision of the region. This paper aims to understand how those political leaders are giving meaning to the regional scale, linking it in their discourses with others administrative levels, with a particular emphasis on the case of European Union. For this purpose, I applied lexical analysis and research for specific vocabulary to a corpus of 8 speeches pronounced by the newly elected presidents of the regions Emilia-Romagna and Lazio between 2000 and 2015. It appears that the necessity of positioning in the relations of power between scales of government varies according to time or political leader’s interests. The analysis also shows that discourses in Emilia-Romagna contain much more references to European Union than those in Lazio, which are more interested in the national scale. This could mean a difference in the Europeanness level of their political elites.